The case of the Green River Killer - Yancey, Diane. frey50 (Detroit, MI : Lucent Books : Thomson/Gale, 2007)
Describes the investigation and prosecution of the Green River serial murderer in Washington State.
Introduction: a twenty year quest -- The victims: daughters of the night -- The investigation: tracking an elusive killer -- The suspects: so many possibilities -- The obstacles: the case bogs down -- Arrest and confession: the mind of a killer.
Keywords: Ridgway, Gary Leon, -- 1949-; Serial murders -- Washington (State) -- Green River Region (King County); Serial murder investigation -- Washington (State); Serial murderers -- Washington (State) -- Green River Region (King County) -- Psychology